Caregivers Experiences about elderly with type 2 diabetes mellitus during the COVID-19 pandemic - Catalán Gómez, Carlos Alberto (Universidad de Sonora, 2022)
Introduction: Currently, the presence of the COVID-19 pandemic has impacted the entire population, affecting patients with chronic diseases such as type 2 diabetes mellitus to a greater extent, which implies a greater burden for their main caregivers. Objective: Identify the experiences in caregivers of older adults with type 2 diabetes mellitus during the COVID-19 pandemic. Methodology: Qualitative descriptive study of a phenomenological type based on the lived experience and perceptions of seven caregivers over 18 years of age of patients with type 2 diabetes mellitus, a structured interview was applied in six dimensions, the data were analyzed with the statistical program Atlas Ti version 7.0, the study adhered to the provisions set forth by General Health Law on Health Research. Results: The caregivers reported being between 18 and 40 years old, mostly men, the length of care ranged from 1 to 20 years; regarding the handling of the information, they stated ignorance with respect to care, and regarding the negative experience in the care during pandemics. In this respect, caregivers perceived situations of stress and generation of strategies for coping with confinement, in the social environment stress and anxiety prevailed; regarding the feeling of satisfaction with care they mentioned being satisfied. Conclusion: A difficult, frustrating, awful, disturbing, scary, and exasperating experience was identified at the time of the COVID-19 pandemic, as well as lack of attention towards caregivers who were prone to suffering from an overload disorder.